Святий Феодор Стратилат і русько-візантійські війни - Fylypchuk, Oleksandr (Чернівецький національний університет імені Юрія Федьковича, 2021)
The article discusses the function of memory of saint Theodore Stratelates as a protector on the battlefield in the Rus’-Byzantine wars. A thorough analysis of the evidence found in the Life of Saint Basil the Younger, History of Leo the Diacon, Synopsis of John Skylitzes and the Rus’ian Primary Chronicle leads us to conclude that Theodore Stratelates’ memory was created after the attack of Rus’ on the Constantinople in 941 and the campaign of John Tzimisces against the Rus’ in 971. The comparison of sources (the Life of Saint Basil the Younger and the Rus’ian Primary Chronicle) carried out by the author enables to think that the strategos Theodore in the narrative of the Life of Saint Basil the Younger was a saint. The study of both cases shows that the war of emperor John Tzimisces with the Rus’ of Svjatoslav the Glorious changed the geography of the cult of Theodore Stratelates. The attention is paid to the sources of two Byzantine narratives (the History of Leo the Diacon and a Synopsis of John Skylitzes) about the role of Theodore Stratelates in the battlefield at Dorostolon. As such the renaming of Dorostolon to Theodoropol became part of the military ideology of emperor John Tzimisces, being its apology of the cult of Theodore Stratelates in this land. This gives some grounds for assuming that this change of the geography of the cult in Dorostolon greatly influenced later chroniclers such as author of the Rus’ian Primary Chronicle.
Keywords: святий Феодор, Русь, Візантія, Константинополь, Доростол, Святослав Cлавний, Іоанн Цимісхій